Study of The Use of Dominance Principle in The Asymmetrical Composition (Case Study: Works of Two Dimensions of DKV Students FSRD UK Maranatha) - Setiawan, Hendra (Universitas Ciputra, 2017)
Due to being an expert in unifying elements in a composition is a must for a designer, design students are required to learn the principles of organization. Comprehending the principles well would enable them to design an effective composition. One of the principles of organizations they need to grasp is dominance. Dominance would create certain visual emphasis in a composition that would avoid confusion for the viewers in determining the visual priority of the elements in a composition. Without dominance a composition would be visually “flat”, having no clear visual hierarchy. There are various ways in achieving dominance, but students do not seem to have applied enough variations in creating dominance in their compositions. Accordingly, this research focuses in analyzing the different ways the students have used in forming dominance in their compositions and how to help them explore more the different ways in forming the dominance. The short-term goal in this research is learning the application of dominance as one of the seven principles of organization by deeply analyzing the different ways in creating it. The long-term goal is to help students effectively create visual compositions in various ways. This research would use the qualitative descriptive method by showing the students’ works and analyzing them.